PENINGKATAN KEMAMPUAN MENULIS DENGAN GAMBAR SISWA SMK MUHAMMADIYAH KELAS XI JURUSAN TEKHNIK OTOMOTIF KOTA PEKANBARU - Syaifullah, Syaifullah (Jurnal Ilmu Budaya, 2011)
At vocational high school Muhammadryah 1 Automotive class Pekanbaru, the researcher has found that student have low writing skills. One of the factor is is the Students' low vocabulary mastery. For the data clarification, the researcher did a research there. It was a Classroom Action Research (CAR). The aimresearcher has found that the students have low writing skills. One e the factors is